2020
DOI: 10.21203/rs.3.rs-38142/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the Immediate Impact of COVID-19 Lockdown on the Air Quality of Kolkata and Howrah, West Bengal, India

Abstract: Abstract The worldwide spread of COVID-19 caused a nationwide lockdown in India from 24th March 2020 and was further extended up to 3rd May 2020 to break off the transmission of novel Coronavirus. The study is designed to assess the changes in air quality from the pre lockdown period to the during lockdown period in Kolkata and Howrah municipal corporation, West Bengal, India. GIS-based techniques include the spatial and temporal distribution of pol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 56 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…After a quick review of the previously published studies on the assessment of air pollution level, few notable research gaps have been identified. First , the previous research studies on the assessment of air quality have focused on particular megacities such as Delhi ( Mahato et al, 2020 ; Khan, 2020 , Sikarwar et al, 2020 ) and Kolkata ( Sarkar et al, 2021 ), but very few studies were performed on the relationship between particulate matter concentration and meteorological parameters ( Dhaka et al, 2020 ). Second, although many recent studies have been performed to assess air pollution levels in India during lockdown phases ( Mahato and Ghosh, 2020 ; Sharma et al, 2020 ), very few studies have been carried out during the progression of the unlock phases of lockdown in India ( Ravindra et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…After a quick review of the previously published studies on the assessment of air pollution level, few notable research gaps have been identified. First , the previous research studies on the assessment of air quality have focused on particular megacities such as Delhi ( Mahato et al, 2020 ; Khan, 2020 , Sikarwar et al, 2020 ) and Kolkata ( Sarkar et al, 2021 ), but very few studies were performed on the relationship between particulate matter concentration and meteorological parameters ( Dhaka et al, 2020 ). Second, although many recent studies have been performed to assess air pollution levels in India during lockdown phases ( Mahato and Ghosh, 2020 ; Sharma et al, 2020 ), very few studies have been carried out during the progression of the unlock phases of lockdown in India ( Ravindra et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the standard conceptualization of a nineteenth-century Bengal Renaissance characterized by a literary efflorescence, initiatives for social reform and the undermining of Hindu orthodoxy (all engendered by Western influence), see the pseudonymously published 1946 essay by the historian Susobhan Sarkar (Sen 1946) and the additional material in Sarkar (1979). Few historians today would agree unreservedly with Sarkar's interpretation, however; for a review of recent and ongoing debates on the topic, see Hatcher (2001).…”
mentioning
confidence: 99%